2017
DOI: 10.1007/s10995-017-2320-1
|View full text |Cite
|
Sign up to set email alerts
|

The Use of ACOG Guidelines: Perceived Contraindications to IUD and Implant Use Among Family Planning Providers

Abstract: SignificanceThe American College of Obstetricians and Gynecologists (ACOG) provides up to date guidelines for the use of longacting reversible contraception methods (LARC); however, there is limited information on how these guidelines are used by practitioners. In this paper, we describe the differences in providers' beliefs and practices before and after the release of the 2012 ACOG guidelines and how these might be contributing to the limited use of LARC in the US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…The IUD is an effective contraceptive method that is currently underused by providers who hold invalid beliefs; however, these providers' can enhance their knowledge through continuing education. 6 This current study confirms the findings of Thompson et al 15 that measured the positive effect of provider LARC education and reinforces the need for continued training to translate best practices into clinical practice. Our educational intervention yielded an increase in provider beliefs that favor IUD provision and in providers' IUD use, echoing other research findings.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The IUD is an effective contraceptive method that is currently underused by providers who hold invalid beliefs; however, these providers' can enhance their knowledge through continuing education. 6 This current study confirms the findings of Thompson et al 15 that measured the positive effect of provider LARC education and reinforces the need for continued training to translate best practices into clinical practice. Our educational intervention yielded an increase in provider beliefs that favor IUD provision and in providers' IUD use, echoing other research findings.…”
Section: Discussionsupporting
confidence: 89%
“…10 These findings are consistent with the current literature affirming the need for provider training and updated knowledge of IUDs. 6,14 Health care providers' biases and long-held misconceptions on the safety of the IUD exist in practice currently. 7 Kohn et al 7 examined the likelihood of providers to recommend the IUD to patient groups and reported that only 58% of providers would recommend the IUD to nulliparous women and that only 55% would recommend the IUD to women younger than 20 years.…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Midwives have a role in the ongoing education of the interprofessional women's health care team. Consistency in women's health care providers’ translation of IUD best practices into clinical practice needs improvement 8,20 . It is important to ensure all health care providers, including those who provide primary and pediatric care, are aware that the use of IUDs is recommended for young women and that STIs are not a contraindication for IUD use or continuation 1,15,21 …”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…The rate of unintended pregnancy may be reduced by women's health care providers offering IUD counseling and provision 7 . In the context of the STIs N gonorrhoeae and C trachomatis , some health care providers may not to adhere to IUD best practices 8 . This article reviews evidence‐based care for women with, or seeking, an IUD while experiencing a gonococcal infection, chlamydial infection, or PID.…”
Section: Introductionmentioning
confidence: 99%